2021
DOI: 10.3390/diagnostics11020269
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Exosomes in Ischemic Heart Disease—A Narrative Review

Abstract: Ischemic heart disease (IHD) is the primary cause of death globally. IHD is associated with the disruption of blood supply to the heart muscles, which often results in myocardial infarction (MI) that further may progress to heart failure (HF). Exosomes are a subgroup of extracellular vesicles that can be secreted by virtually all types of cells, including cardiomyocytes, cardiac fibroblasts, endothelial cells, and stem and progenitor cells. Exosomes represent an important means of cell–cell communication throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 165 publications
0
8
0
Order By: Relevance
“…In addition to hard-wired neural pathways between cardiopulmonary regions and the brain, there are novel non-neural communication pathways that can modulate autonomic tone. Extracellular vesicles (EVs) are a prime example of such communication ( 23 ). Transfer of proteins, lipids, nucleotides, and metabolites from one organ to another is mediated by EV cargo, specific to each tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hard-wired neural pathways between cardiopulmonary regions and the brain, there are novel non-neural communication pathways that can modulate autonomic tone. Extracellular vesicles (EVs) are a prime example of such communication ( 23 ). Transfer of proteins, lipids, nucleotides, and metabolites from one organ to another is mediated by EV cargo, specific to each tissue.…”
Section: Introductionmentioning
confidence: 99%
“…With cardiac coronary atherosclerosis as the main underlying disease, plaque rupture in the coronary artery triggers coagulation reaction induces platelet aggregation, and then thrombosis in the vascular lumen and progresses along with the blood flow, ultimately leading to acute ischemic hypoxia necrosis of cardiomyocytes downstream of the blood vessel [ 81 ]. The physiological and pathological mechanisms leading to ischemic injury of heart tissue are diverse, among which metabolic acidosis, Ca 2+ overload and accumulation of ROS are the core elements caused by hypoxia and insufficient supply of essential nutrients for some cells [ 82 ]. A series of physiological and pathological changes induced by AMI can stimulate various heart cells and then affect the EXOs they secrete.…”
Section: Factors Affecting Cardiogenic Exosmentioning
confidence: 99%
“…In recent years, treatments for MIRI have included ischemic preconditioning (IPC), ischemic postprocessing (IPost), remote ischemic conditioning (IPC), the use of drugs to prevent myocardial reperfusion injury, therapeutic hyperbaric oxygen (HBO) and hypothermia (77)(78)(79). Recent studies have shown that the cardioprotective effect of IPC is mediated by exosomes (80). For example, exosomes derived from rat fibroblasts can protect cardiomyocytes after ischemia by targeting MIR-423-3p/RAP2C to reduce MIRI (81).…”
Section: Myocardial Ischemia-reperfusion Injurymentioning
confidence: 99%